Study on the pathogenicity and immunogenic capacity of the microorganism Fusobacterium necrophorum - Andrei Nanu; Constantin Chiurciu; Costin Stoica (Medicamentul Veterinar)
This study is aiming veterinarians, researchers and breeders of sheep, goats and cattle, and aims to present an effective prophylactic method in the fight against necrobacillary pododermatitis. The pathogenicity and the determination of the minimum lethal dose in mice facilitated the demonstration of the immunogenic capacity and protective effect of an inactivated suspension of Fusobacterium necrophorum. Vaccination of sheep and goats against necrobacillosis induced an increase in antibodies by at least 2log2, evidenced by the slow seroagglutination reaction in the tubes. The reduction to extinction of cases of necrobacillary pododermatitis in sheep herds certifies the immunizing efficacy of the vaccine suspension.